Chironomidae (Diptera) community structure in two subsystems with different states of conservation in a floodplain of southern Brazil Estrutura da comunidade de Chironomidae (Diptera) em dois subsistemas em diferentes estados de conservação de uma planície de inundação do sul do Brasil - Gisele Cristina Rosin; Danielle Paula de Oliveira Mangarotti; Alice Michiyo Takeda (Acta Limnologica Brasiliensia, 2010)
AIM: Our study aimed to compare the composition, distribution, diversity, abundance and dominance of Chironomidae in two subsystems of the Upper Paraná River floodplain, with different levels of conservation. We expected to find the highest values of diversity and lowest dominance of taxa in the most conserved areas (Ivinhema subsystem). We also expected to detect differences in the composition and distribution of communities between the subsystems, because of the level of conservation of each subsystem; METHODS: Sampling was performed in March and September 2003, in eight stations, four in the Paraná River subsystem and four in the Ivinhema River subsystem. Four samples were taken at each point with a modified Petersen-type sampler: three for biological analysis and one for sedimentological analysis. Chironomidae larvae were identified to generic level; RESULTS: Twenty-nine genera belonging to three subfamilies (Tanypodinae, Chironominae and Orthocladiinae) were recorded in this study. Chironomus, Dicrotendipes, Goeldichironomus, and Tanypus were the main genera found in the Paraná subsystem. Polypedilum was the only genus present in all sampling stations, and was dominant in five of them. In the Paraná subsystem we observed the highest values of dominance, and in the Ivinhema subsystem the largest number of rare taxa; CONCLUSIONS: Results showed differences in the structure of the Chironomidae community between the Paraná and Ivinhema subsystems. The community of Chironomidae in the Paraná subsystem was composed predominantly by generalist and tolerant genera. In the Ivinhema subsystem we observed higher richness of taxa. The greatest diversity, lowest values of dominance and exclusive taxonomic composition in the Ivinhema River subsystem could be reflecting a less degraded environment, demonstrating that the conservation of these areas is essential for maintaining the diversity of Chironomidae. OBJETIVO: Esse estudo teve por objetivo comparar a composição taxonômica, distribuição, diversidade, abundância e dominância da comunidade de Chironomidae em dois subsistemas da Planície de inundação do alto rio Paraná em diferentes estados de conservação. Esperava-se encontrar maiores valores de diversidade e menor dominância de táxons nas áreas mais conservadas (subsistema Ivinhema). Esperava-se também, diferenças na composição e na distribuição da comunidade entre os subsistemas devido a aos diferentes estados de conservação de cada estação; MÉTODOS: As coletas foram realizadas em março e setembro de 2003 em oito ambientes, quatro no subsistema Paraná e quatro no subsistema Ivinhema. Em cada ponto foram coletadas quatro unidades amostrais por período com um pegador do tipo Petersen modificado: três para análise biológica e uma para análise sedimentológica. As larvas de Chironomidae foram identificadas no nível de gênero; RESULTADOS: Foram registrados 29 gêneros pertencentes a três subfamílias de Chironomidae. Chironomus, Dicrotendipes, Goeldichironomus, e Tanypus foram os principais representantes do subsistema Paraná. Polypedilum foi o único gênero presente em todas as estações de amostragem e dominante em cinco delas. No subsistema Paraná foram observados maiores valores de dominância e no subsistema Ivinhema maior número de espécies raras; CONCLUSÕES: Os resultados demonstraram diferenças na estrutura da comunidade de Chironomidae entre os subsistemas Paraná e Ivinhema. A composição de Chironomidae no subsistema Paraná foi predominantemente de gêneros considerados generalistas e tolerantes. No subsistema Ivinhema foi observado maior riqueza de táxons. A maior diversidade no subsistema Ivinhema pode ser um reflexo de ambientes menos degradados, mostrando que a preservação dessas áreas é determinante para a manutenção da abundância e da diversidade de Chironomidae.